Hilar Mossy Cells Provide the First Glutamatergic Synapses to Adult-Born Dentate Granule Cells - Chancey, Jessica H. (Society for Neuroscience, 2014)
Adult-generated granule cells (GCs) in the dentate gyrus must establish synapses with preexisting neurons to participate in network activity. To determine the source of early glutamatergic synapses on newborn GCs in adult mice, we examined synaptic currents at the developmental stage when NMDA receptor-mediated silent synapses are first established. We show that hilar mossy cells provide initial glutamatergic synapses as well as disynaptic GABAergic input to adult-generated dentate GCs.